Quantum calibrations traceable through classical radiometry. (December 2021) - Stephens, Michelle; White, Malcolm G.; Gerrits, Thomas; Tomlin, Nathan A.; Lehman, John H.
Abstract: A system for calibrating single photon detector efficiency that is traceable to the SI through a state-of-the-art classical optical fibre radiometer has been developed and is in the process of being vetted as a calibration service at the National Institute of Standards and Technology (NIST). The method of calibration is direct substitution to power meters relative to NIST's optical fibre cryogenic primary standard and builds on the existing measurement infrastructure for the calibration of optical fibre power meters. Recent improvements to the optical fibre cryogenic radiometer make it more robust and deployable. The traceability of the single photon detector calibration service under development to these classical measurements is discussed, along with a description of the technique used in this calibration service to calibrate the detection efficiency of single photon detectors. Finally, we discuss work on the development of these technologies so that in the future they may be deployable to the point-of- use.